The concept of derogation and its place in the system of restrictions on human rights - Bochkovoi, V. O. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
This article is devoted to the analysis of the legal nature, scope, and conditions for the application of derogation from human rights. It explores international standards governing the temporary suspension by states of certain human rights obligations, primarily under the International Covenant on Civil and Political Rights of 1966 and the European Convention on Human Rights of 1950. The author examines doctrinal approaches to the concept of derogation and identifies the key criteria for its lawfulness, including the existence of a public emergency threatening the life of the nation, the official proclamation of a state of emergency, the proportionality and necessity of measures taken, the temporary nature of such measures, and compliance with other international obligations. It is emphasized that several essential conditions must be met for derogation to be lawful: the existence of a real and serious emergency; the necessity and proportionality of the measures; consistency with other international obligations; non-discrimination; and the requirement of official notification to relevant international bodies. The article underlines that derogation may not extend to certain non-derogable rights, such as the right to life; the prohibition of torture and cruel, inhuman or degrading treatment or punishment; the prohibition of slavery and servitude; and the prohibition of punishment without law. The jurisprudence of the European Court of Human Rights is analyzed, as it plays a key role in shaping the standards of lawful derogation and underscores the importance of effective control to prevent abuse by states. It is concluded that derogation constitutes a legal mechanism that allows a state to temporarily depart from certain international human rights obligations in times of public emergency threatening the life of the nation.